Comparative study of needle penetration forces in sewing hems on toweling terry fabrics: influence of needle type and size - Carvalho, Manuel (2020)
In this paper, an industrial case study comparing the use of different needles in the production of hems in towels is presented. The study aims to assess the sewability of the fabrics, quantified by needle penetration forces. The market offers an interesting range of options for the needle, regarding the geometry of the needle point, surface finishing, and sizes. However, in practice, the choice is difficult, namely due to the lack of quantitative data that may support the empirical evaluation made by the sewing technicians. The work aims to assess how the needle type and size relate to the resulting needle penetration forces. Three terry fabric structures, produced by a home textiles manufacturer, were tested using needles of different sizes, points, and coatings. Needle penetration forces were measured on a sewability tester prototype, previously designed and developed, based on an instrumented overedge sewing machine. It was found that needle penetration forces present very significant differences with small size increments, needle coating also influences forces significantly, and different needle points produce only slight differences, significant only on some of the fabrics that were tested.